NAT10 promotes cell proliferation by acetylating CEP170 mRNA to enhance translation efficiency in multiple myeloma - Rongfang Wei; Xing Cui; Jie Min; Zigen Lin; Yanyan Zhou; Mengjie Guo; Xiaojuan An; Hao Liu; Siegfried Janz; Chunyan Gu; Hongbo Wang; Ye Yang (Elsevier, 2022)
Multiple myeloma (MM) is still an incurable hematologic malignancy, which is eagerly to the discovery of novel therapeutic targets and methods. N-acetyltransferase 10 (NAT10) is the first reported regulator of mRNA acetylation that is activated in many cancers. However, the function of NAT10 in MM remains unclear. We found significant upregulation of NAT10 in MM patients compared to normal plasma cells, which was also highly correlated with MM poor outcome. Further enforced NAT10 expression promoted MM growth in vitro and in vivo, while knockdown of NAT10 reversed those effects. The correlation analysis of acetylated RNA immunoprecipitation sequencing (acRIP-seq) and ribosome profiling sequencing (Ribo-seq) combined with RIP-PCR tests identified centrosomal protein 170 (CEP170) as an important downstream target of NAT10. Interfering CEP170 expression in NAT10-OE cells attenuated the acceleration of cellular growth caused by elevated NAT10. Moreover, CEP170 overexpression promoted cellular proliferation and chromosomal instability (CIN) in MM. Intriguingly, remodelin, a selective NAT10 inhibitor, suppressed MM cellular growth, induced cellular apoptosis in vitro and prolonged the survival of 5TMM3VT mice in vivo. Collectively, our data indicate that NAT10 acetylates CEP170 mRNA to enhance CEP170 translation efficiency, which suggests that NAT10 may serve as a promising therapeutic target in MM.